2001
DOI: 10.1507/endocrj.48.19
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Adrenocorticotropin Syndrome Exhibiting Paradoxical Adrenocorticotropin Responsiveness to Gonadotropin-Releasing Hormone.

Abstract: Abstract.In a 37-year-old man who had Cushing's syndrome, investigations, including overnight dexamethasone suppression test, corticotropin-releasing hormone (CRH) test, pituitary MRI and inferior petrosal sinus sampling suggested the presence of ectopic adrenocorticotropin (ACTH) production. Interestingly, gonadotropin-releasing hormone (GnRH) increased plasma ACTH from 73 pg/ml to 708 pg/ml at 15 min. Furthermore, desmopressin also increased plasma ACTH whereas CRH and thyrotropin-releasing hormone (TRH) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In addition, plasma ACTH did not respond to TRH in two of the examined patients. Ujihara et al reported that in a patient who had Cushing's syndrome, TRH and CRH had no effect on the secretion of ACTH, whereas GnRH increased plasma ACTH levels [14]. Including this report, it is therefore possible to speculate that no response of ACTH to TRH may be due to the lack of TRH receptors in ACTH cell adenoma.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, plasma ACTH did not respond to TRH in two of the examined patients. Ujihara et al reported that in a patient who had Cushing's syndrome, TRH and CRH had no effect on the secretion of ACTH, whereas GnRH increased plasma ACTH levels [14]. Including this report, it is therefore possible to speculate that no response of ACTH to TRH may be due to the lack of TRH receptors in ACTH cell adenoma.…”
Section: Discussionmentioning
confidence: 68%
“…Reverse transcription was performed by incubating 1 mg total RNA with 1 ml of PowerScript reverse transcriptase (Clontech, USA) and 1 ml of 0.5 mg/ml oligo(dT) [12][13][14][15][16][17][18] primer (Life Technologies, USA) at 42°C for 70 minutes in 20 ml reaction buffer. RT products were diluted ten times with 10 mM Tricine-KOH (pH 9.2)/0.1 mM EDTA, and stored at -20°C until used for PCR.…”
Section: Histological Studiesmentioning
confidence: 99%
“…The underlying mechanism of ACTH response by desmopressin could be accounted for by the amount of V1bR expressed by ACTH-producing tumors irrespective of pituitary or non-pituitary origin [6,23,25]. There have been only two cases of desmopressin-responsive EAS associated with thymic NET thus far reported in the English literature [26,27].…”
Section: Discussionmentioning
confidence: 99%